Perception of Online Learning Among Students From India Set Against the Pandemic - Bast, Felix (Frontiers in Education, 2021)
India is the second-most populous country in the world. There had been a tremendous shift towards online learning through Indian Government’s digital initiatives in general, and during COVID-19 lockdown in particular. An online self-report survey (n = 1,318) was conducted to assess students’ perception of online learning in this changed situation in comparison with traditional classroom learning. The study analysed eight independent variables on student’s perception towards online learning, viz., gender, nature of the settlement, economic background, religiosity, primary electronic device, technology-receptiveness, age, and educational institution, with each of these variables forming respective research hypotheses. Results revealed several exciting facets of students’ perceptions. Receptiveness towards online learning was significantly higher for students from urban areas compared with rural areas. Possible reasons for these results are discussed, impediments to student’s motivation with digital education are identified and the findings are contextualized in a broader perspective.